Effect of sodium caseinate on hindgut fermentation and fiber digestion in the equine and Effect of Megasphaera elsdenii on broiler chick performance - Jordan, Katherine Van (Kansas State University, 2017)
Eight cecally cannulated horses were used in a replicated, 4 x 4 Latin square design conducted in 4, 14-d periods to determine effects of sodium caseinate on equine hindgut fermentation and fiber digestion. Horses were maintained on an ad libitum diet of Smooth Bromegrass hay and treatments consisted of cecal infusions of water (CON), 0.125 g sodium caseinate/kg BW (LOW), 0.25 g sodium caseinate/kg BW (MED), and 0.50 g sodium caseinate/kg BW (HI). Cecal NH3 concentrations increased (P < 0.01) as casein increased. Horses on the CON and MED treatments had greater cecal pH (P < 0.01) than horses on the LOW and HI treatments; however, there was no effect of treatment of fecal pH. Dry matter, OM, NDF, and ADF digestibility were unaffected by treatment (P > 0.10). There were no differences in dry matter intake (DMI), regardless of treatment. There was no treatment effect on cecal acetate, propionate, butyrate, total VFA concentration or acetate:propionate (A:P) ratio. Inter-horse variability and a small sample size may contribute to the lack of statistical differences amongst treatments. Results from this study may imply that medium quality, roughage based protein supplies an adequate level of nitrogen to the microflora of the hindgut. A performance study was conducted to evaluate the effect of strain and method of administration of Megasphaera elsdenii on growth performance in broiler chickens. In Experiment 1, pens were randomly assigned to 1 of 6 treatments: 0.2 mL oral gavage containing 1.97 x 10⁹ CFU/mL of M. elsdenii strain NCIMB 41125 (Lactipro, MS-Biotec, Wamego, KS; O-L), 0.2 mL of fresh culture containing 0 CFU/mL of M. elsdenii strain KS 249 (O-KS; Attempts to grow this strain were unsuccessful), 0.2 mL of a fresh culture containing 1.06 x 10⁹ CFU/mL of M. elsdenii strain B52-2083 (O-B52), aerosolized mist at rate of 15 mL per pen containing 1.97 x109 CFU/mL of M. elsdenii strain NCIMB 41125 (~1.88 mL/bird; MS-Biotec, Wamego, KS; OM), topdressing (mixture of diet and freeze dried M. elsdenii strain NCIMB 41125; TD) containing 1.18 x 10⁷ CFU/g of M. elsdenii strain NCIMB 41125 at a rate of a quarter teaspoon per bird, or negative control that had no contact with the probiotic product. Broilers across all treatment groups showed similar ADFI (P = 0.82), ADG (P = 0.89), gain:feed (P = 0.93), and mortality rates (P = 0.54). In Experiment 2, chicks were assigned to 1 of 2 treatments consisting of lyophilized M. elsdenii strain NCIMB 41125 in the form of a topdressing (TD) or a negative control that had no contact with the probiotic product (C). Average daily gain (P = 0.02) and gain:feed (P = 0.04) were both greater in birds receiving the TD when compared to the C birds. Feed intake (P = 0.70) and mortality rates (P = 0.31) were not different between treatments. Administration of lyophilized M. elsdenii strain NCIMB 41125 may be an effective means to improve growth rate and feed efficiency of broiler chicks.
Keywords: Equine; Sodium caseinate; Digestibility; Megasphaera elsdenii; Poultry; Probiotic